Analisis Faktor-Faktor yang Mempengaruhi Perubahan Indeks Harga Saham Individual di Bursa Efak Jakarta Tahun 1996-1997 - Gita Danupranata (LP3 UMY, 2015)
This is an empirical research, which analyzed Jactors lhat dfected the change in Individua! Stock Price Index in the Jakarta Stock Exchange in 1996'1997. It was assumed lhat Price Earning Ratio, Dividend Layout Ratio, Debt to Equity Ratio, Return on Investment, Rel m on Equity and Liquidity are lactors that played important role in aflecling the price change.